AN IMPROVED METHOD FOR ISOLATION OF THIELAVIOPSIS PARADOXA FROM STEM BLEEDING AFFECTED COCONUT PALMS - Anil Kumar; K.K.N. Nambiar (International Coconut Community, 1991)
Stem bleeding of coconut caused by Thielaviopsis paradoxa (de Seynes) Von Hohnel is an important disease affecting coconut in many countries (Menon and Pandalai, 1958; Ohler, 1966, Nambiar and Sastry, 1988). lsolation of the pathogen from diseased tissues on different agar based media has given inconsistent results (Anon., 1976; Anon., 1986), None of the selective media reported for certain related fungi viz., T. basicola (Berk and Br.) Ferr. (David, 1978;Tsao and Bricker, 1966) and Ceratocystis wagnerii Goheen and Cobb (Hicks et al., 1980) proved useful for the isolation of T. paradoxa Since, standardization of an isolation method is a basic necessity for any study on plant pathogens, an attempt was made to improve upon existing methods.